Molecular studies of cold active lipase and protease - Mohamad Ali, Mohd. Shukuri; Raja Abd. Rahman, Raja Noor Zaliha; Alias, Norsyuhada; Salleh, Abu Bakar; Basri, Mahiran (Nova Science Publishers, Inc., 2013)
Psychrophilic organisms produce enzymes adapted to function at low temperature. These enzymes are characterized by a catalytic efficiency at low and moderate temperatures but are rather thermolabile. Thermophilic enzymes usually feature in discussion of industrial uses because their heat-stability makes them ideal biocatalyst for many reactions. However, cold-active/heat-labile enzymes also have great potential in industry. Cold-active enzymes might offer novel opportunities for biotechnological exploitation based on their high catalytic activity at low temperatures, low thermostability and unusual specificities. These properties are of interest in diverse fields such as detergents, fabric and food industry, bioremediation and biocatalysts under low water conditions. Furthermore, fundamental issues concerning the molecular basis of cold activity and the interplay between flexibility and catalytic efficiency are of important in the study of structure-function relationships in protein. By means of X-ray crystallography, these properties are beginning to be understood, and the rules governing their adaptation to cold appear to be relatively diverse. To date, extensive studies on psychrophilic enzymes were conducted ranging from purification and characterization, molecular cloning and expression, homology modeling and structural studies and x-ray crystallography studies. Lipases and protease which represents the most important groups of extracellular hydrolytic enzymes were examined due to the attractive properties of these enzymes that constitute a tremendous potential for fundamental research and biotechnological applications.